Hubungan Citra Tubuh dan Harga Diri pada Perempuan Pengguna Tiktok Usia 18-24 Tahun - Luthfania Luthfania; Oktavia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Teknologi Nusantara, 2026)
This study aimed to determine the effect of psychopressure therapy on anxiety in the elderly at the Wijaya Kusuma 2 Posyandu, Sindangsari, Bogor. Conducted over 14 days, this study used a pretest and postest experimental design with 15 respondents experiencing anxiety. Primary data were obtained through the Geriatric Anxiety Inventory (GAI) questionnaire, while secondary data were obtained from Posyandu visit records. The results showed that 6 respondents (40.0%) experienced mild anxiety, 7 respondents (46.7%) moderate anxiety, and 2 respondents (13.3%) severe anxiety before the intervention. After psychopressure therapy, 7 respondents (46.7%) experienced no anxiety, 6 respondents (40.0%) experienced moderate anxiety, 2 respondents (13.3%) experienced mild anxiety, and none experienced severe anxiety. A paired t-test yielded a p-value of 0.000, indicating that psychopressure therapy at HT 7 (shenmen) and PC 6 (neiguan) points was effective in reducing anxiety in the elderly. This finding highlights the importance of both physical and psychological interventions to improve the physical and mental well-being of the elderly.